2013
DOI: 10.1016/j.cell.2013.11.025
|View full text |Cite
|
Sign up to set email alerts
|

A Bidirectional Circuit Switch Reroutes Pheromone Signals in Male and Female Brains

Abstract: SummaryThe Drosophila sex pheromone cVA elicits different behaviors in males and females. First- and second-order olfactory neurons show identical pheromone responses, suggesting that sex genes differentially wire circuits deeper in the brain. Using in vivo whole-cell electrophysiology, we now show that two clusters of third-order olfactory neurons have dimorphic pheromone responses. One cluster responds in females; the other responds in males. These clusters are present in both sexes and share a common input … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
237
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(247 citation statements)
references
References 58 publications
9
237
0
1
Order By: Relevance
“…Interestingly, both females and males express OR67d and OR65a, and these receptors respond equally to cVA in both sexes (Kurtovic et al, 2007;Van der Goes van Naters and Carlson, 2007). However, the neuronal circuit underlying OR67d is sexually dimorphic and, consequently, different neuronal cluster are activated in males and females (Datta et al, 2008;Ruta et al, 2010;Kohl et al, 2013 Table 2). …”
Section: Chemoreceptors and Sexual Behavior: Relevance Of Pheromone Amentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, both females and males express OR67d and OR65a, and these receptors respond equally to cVA in both sexes (Kurtovic et al, 2007;Van der Goes van Naters and Carlson, 2007). However, the neuronal circuit underlying OR67d is sexually dimorphic and, consequently, different neuronal cluster are activated in males and females (Datta et al, 2008;Ruta et al, 2010;Kohl et al, 2013 Table 2). …”
Section: Chemoreceptors and Sexual Behavior: Relevance Of Pheromone Amentioning
confidence: 99%
“…Moreover, the precise and complete network from the detection of a chemical at the periphery to the muscle cells that lead to a behavioral output is still partially described. Some recent studies on cVA detection have started to decipher this network (Kohl et al, 2013), and have shown that this cVA circuit seems to be interconnected with other sensory modalities such as hearing (Zhou et al, 2014) which highlights the importance of the connectivity between modalities.…”
Section: Perspectivesmentioning
confidence: 99%
“…There is a sex-specific processing component to the response to cVA (Ruta et al, 2010;Kohl et al, 2013). While cVA has a suppressive effect on male courtship, it acts as an aphrodisiac to females, who mate quicker with males when they sense this pheromone (Kurtovic et al, 2007;Ronderos and Smith, 2010).…”
Section: A Second Pheromonal System: Cis-vaccenyl Acetatementioning
confidence: 99%
“…The functional connectivity between neurons that is demonstrated by measuring GECI responses cannot indicate whether the connections are direct, and it is always possible that intermediate neurons are involved. To distinguish between the possibilities of monosynaptic versus polysynaptic connectivity, as well as to characterize the physiological properties of the functional connection, electrophysiology experiments are required (Gruntman and Turner 2013;Kohl et al 2013;Fişek and Wilson 2014;Tuthill and Wilson 2016).…”
Section: Assessing Functional Connectivity Among Neuronsmentioning
confidence: 99%